Evaluation of practice guidelines and preservation of the submandibular gland in neck dissection - Rafael Michel Coca Granado; Denia Morales Navarro; Yuniesky Jiménez Rodríguez (Editorial Ciencias Médicas, 2023)
Introduction: Practical guidelines for head and neck cancer care currently address the functional preservation of some organs within oncospecific treatment. Objectives: To evaluate clinical practice guidelines and how they address the preservation of the submandibular gland in neck dissection. Methods: A quantitative, descriptive and cross-sectional research was carried out to evaluate six guidelines for head and neck cancer care, in terms of their methodological quality and the preservation of the submandibular gland in neck dissection. The Appraisal of Guidelines Research and Evaluation instrument was used, a team was composed by four evaluators who gave their consent and were trained to use such instrument. For the analysis of the information, the Statistical Package for Social Sciences version 21 was used and the quality score for each domain and the intraclass correlation coefficient were calculated. Results: The highest quality score corresponded to domains 1, 4 and 6. The guide with the highest quality score was that of the European Society of Medical Oncology reporting an average of 94.3%, while that of the Chinese Society of Clinical Oncology obtained the lowest value (71.5%). Three guidelines had the highest quality score (7) in the global evaluation. The highest strength of agreement between the evaluators corresponded to the guideline of the American Society of Clinical Oncology (1) and the lowest to that of the National Institute of Oncology and Radiobiology (0.93). Conclusions: The head and neck cancer clinical practice guidelines evaluated presented high methodological quality and the preservation of the submandibular gland in neck dissection was not addressed in any of them.